HLA-DO is a lysosomal resident which requires association with HLA-DM for efficient intracellular transport. - Liljedahl, M (1996)
The murine MHC class II molecule H2-O is expressed in B-cells and in thymic epithelium but the human equivalent, HLA-DO (DO), has not been detected, though the corresponding genes, HLA-DNA and HLA-DOB, are well known. Here we show DO to be a lysosomal resident in B-cells. Surprisingly, DO forms stable complexes with HLA-DM (DM), another lysosomal class II-like molecule which is important for class II-restricted antigen presentation. Association with DM is necessary for efficient exit of DO from the endoplasmic reticulum (ER) and thus for accumulation in lysosomes. The association is evolutionarily conserved and in mice lacking H2-M, the mouse equivalent of DM, the amount of intracellular H2-O is decreased and only minor amounts of H2-O appear to leave the ER. The DO-DM complexes survive in the lysosomal system suggesting that DO and DM functions may be intertwined.